Silicon-carbon negative electrode material and preparation method and application thereof
By using a combination of porous carbon and nanosilicon in the negative electrode of the battery, combined with long-range carbon nanotubes and carbon coating technology, the charging volume expansion and impedance of silicon materials in the battery are solved, and the high energy density of lithium-ion batteries is achieved and long cycle life.
Patent Information
- Application Number
- CN202411640789.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2024-12-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Silicon materials have huge charging volume expansion and high impedance in the negative electrode applications of battery, which limits its application in terminal products and is difficult to effectively improve the energy density of the battery.
Using a combination of porous carbon materials and nanosilicon, by uniformly distributing long-range carbon nanotubes and nanosilicon in porous carbon, a silicon carbon negative electrode material with high structural strength and low charging volume expansion is formed, and combined with carbon coating treatment to improve the performance of the material. .
It effectively reduces the expansion of lithium-ion batteries, improves cycle life and first reversible capacity, and improves the energy density and structural strength of the battery.
Smart Images

Figure CN119153669A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrode materials, and in particular to a silicon-carbon negative electrode material and a preparation method and application thereof. Background Art
[0002] With the development of consumer electronics, new energy vehicles and electric aircraft, the demand for high energy density and fast charging electrode materials is becoming more and more urgent. At present, commercial graphite negative electrode materials have approached their theoretical gram capacity of 372mA·h / g. Silicon materials have a theoretical gram capacity of up to 4200mA·h / g, and alloying them to form Li 15 Si4, its gram capacity can reach 3579mA·h / g. Therefore, the application of silicon material in battery negative electrode is conducive to greatly improving the energy density of the battery.
[0003] However, while silicon materials have high gram capacity, they are also accompanied by huge charging volume expansion. Excessive volume expansion can easily lead to particle rupture, causing rapid decay of the negative electrode capacity, resulting in a significant reduction in the battery's cycle performance. In addition, silicon, as a semiconductor material, has a large impedance and is prone to large polarization during low-expansion long-cycle charging and discharging processes, limiting its application in terminal products.
[0004] The existing technology relies on the gas phase decomposition deposition of silane. Although it is possible to obtain nano silicon particles of relatively limited size, compared with graphite, they still have a larger volume expansion, which limits the mixing ratio in graphite, making it difficult to effectively improve the energy density of the battery.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] One of the purposes of the present invention is to provide a silicon-carbon negative electrode material with high structural strength and low charging volume expansion.
[0007] The second object of the present invention is to provide a method for preparing a silicon-carbon negative electrode material, which has a simple process, high efficiency, high success rate and is suitable for industrial production.
[0008] The third object of the present invention is to provide an application of a silicon-carbon negative electrode material, which can effectively reduce the expansion of lithium-ion batteries, effectively increase the cycle life of lithium-ion batteries, and achieve outstanding application effects.
[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted: In a first aspect, a silicon-carbon negative electrode material comprises porous carbon and nano-silicon dispersed on the porous carbon; The porous carbon includes pyrolytic carbon and long-range carbon nanotubes dispersed in the pyrolytic carbon; The long-range carbon nanotubes account for 0.1wt% to 5wt% of the silicon-carbon negative electrode material; The long-range carbon nanotubes have a length of 2 μm to 20 μm and a diameter of 1 nm to 100 nm.
[0010] Furthermore, the average particle size D50 of the silicon-carbon negative electrode material is 0.5 μm to 15 μm; Preferably, the pore volume of the silicon-carbon negative electrode material is less than 0.01 cm³ / g, the most probable pore diameter is less than 3 nm, and the specific surface area is ≤5 m² / g.
[0011] Furthermore, the resistivity of the silicon-carbon negative electrode material is 10 mΩ·cm~1000 mΩ·cm.
[0012] Furthermore, the grain size of the nano-silicon is less than 2 nm; Preferably, the nano-silicon accounts for 10wt% to 90wt% in the silicon-carbon negative electrode material.
[0013] In a second aspect, a method for preparing the silicon-carbon negative electrode material described in any one of the above items comprises the following steps: The hard carbon precursor containing long-range carbon nanotubes is pyrolyzed and carbonized and then activated to obtain porous carbon, and nano-silicon is deposited on the porous carbon to obtain the silicon-carbon negative electrode material.
[0014] Furthermore, after the nano-silicon deposition, the method further includes a step of coating the obtained silicon-carbon material; Preferably, the coating treatment comprises carbon coating using a carbon source gas.
[0015] Furthermore, the method for preparing the hard carbon precursor containing long-range carbon nanotubes comprises the following steps: Mixing a carbon source, long-range carbon nanotubes and water to react, dehydrating and polymerizing the carbon source to obtain the hard carbon precursor containing the long-range carbon nanotubes; Preferably, the carbon source comprises at least one of glucose, fructose, galactose, lactose, sucrose, maltose, rice starch, mung bean starch, wheat starch, tapioca starch, corn starch, cellulose and phenolic resin; Preferably, the long-range carbon nanotubes include at least one of acid-treated oligo-walled, single-walled and multi-walled carbon nanotubes; Preferably, the temperature of the mixed reaction is 150°C to 375°C; Preferably, the pressure of the mixed reaction is 2Mpa~8Mpa.
[0016] Furthermore, the temperature of the pyrolysis carbonization is 800°C to 1400°C; Preferably, the pyrolysis carbonization time is 1 h to 12 h.
[0017] Further, the activation treatment includes at least one of a physical activation method and a chemical activation method; Preferably, the gas used in the physical activation method includes at least one of water vapor, air and carbon dioxide; Preferably, the nano-silicon deposition method includes thermal decomposition deposition by silane compounds; Preferably, the temperature of the pyrolysis deposition is 300°C to 800°C; Preferably, the pyrolysis deposition time is 1 h to 12 h.
[0018] A third aspect is an application of the silicon-carbon negative electrode material described in any one of the above items in a lithium-ion secondary battery.
[0019] Compared with the prior art, the present invention has at least the following beneficial effects: The silicon-carbon negative electrode material provided by the present invention has long-range carbon nanotubes uniformly distributed inside the material. The long-range carbon nanotubes have high tensile strength, so they can improve the structural strength of the silicon-carbon negative electrode material, limit its charging volume expansion, and also reduce the charging and discharging impedance of the material; in short, under the joint action of specific long-range carbon nanotubes and their content and nano-silicon grains, the present invention effectively reduces the charging volume expansion, while improving the first reversible capacity and the first efficiency, so that the silicon-carbon negative electrode material has the characteristics of low expansion and long cycle.
[0020] The method for preparing the silicon-carbon negative electrode material provided by the present invention has simple process, high efficiency, high success rate and is suitable for industrial production.
[0021] The application of the silicon-carbon negative electrode material provided by the present invention can effectively reduce the expansion of lithium-ion batteries, effectively increase the cycle life of lithium-ion batteries, and achieve outstanding application effects. BRIEF DESCRIPTION OF THE DRAWINGS In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 A 2000-fold scanning electron microscope image of the silicon-carbon negative electrode material provided in Example 1 of the present invention; Figure 2 This is a 30,000-fold scanning electron microscope image of the silicon-carbon negative electrode material provided in Example 1 of the present invention; Figure 3The first charge and discharge curve of the lithium button cell of the silicon-carbon negative electrode material obtained in Experimental Example 2 of the present invention; Figure 4 This is the first charge and discharge dQ / dV curve of the lithium button cell with the silicon-carbon negative electrode material obtained in Experimental Example 2 of the present invention. DETAILED DESCRIPTION
[0023] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] According to a first aspect of the present invention, there is provided a silicon-carbon negative electrode material, comprising porous carbon and nano-silicon dispersed on the porous carbon; The porous carbon includes pyrolytic carbon and long-range carbon nanotubes dispersed in the pyrolytic carbon; Among them, the proportion of long-range carbon nanotubes in the silicon-carbon negative electrode material can be 0.1wt%~5wt%, and its typical but non-limiting proportions are, for example, 0.1wt%, 0.3wt%, 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt%, and 5wt%. The appropriate proportion of long-range carbon nanotubes can ensure that the silicon-carbon negative electrode material has the characteristics of low expansion and long cycle; if the proportion of long-range carbon nanotubes is too low, the expansion restriction effect is not significant; if the proportion of long-range carbon nanotubes is too high, it will cause problems such as increased specific surface area, reduced capacity and first efficiency.
[0025] It should be noted that the long-range carbon nanotubes are uniformly distributed inside single particles of the silicon-carbon negative electrode material. The long-range carbon nanotubes are in the shape of long ropes, and the length of a single rope can be 2μm~20μm. Typical but non-limiting lengths include 2μm, 4μm, 6μm, 8μm, 10μm, 12μm, 14μm, 16μm, 18μm, and 20μm. It should be noted that if the length of the long-range carbon nanotubes is too short, they cannot play a role in internal binding. If the length of the long-range carbon nanotubes is too long, they cannot be completely wrapped inside the particles. The diameter of the long-range carbon nanotubes can be 1nm~100nm, and typical but non-limiting diameters include 1nm, 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, and 100nm. It should be noted that if the diameter of the long-range carbon nanotubes is too thick, the mechanical properties and conductive properties of the carbon nanotubes cannot be fully exerted.
[0026] The silicon-carbon negative electrode material provided by the present invention has long-range carbon nanotubes uniformly distributed inside the material. The long-range carbon nanotubes have high tensile strength, so they can improve the structural strength of the silicon-carbon negative electrode material, limit its charging volume expansion, and also reduce the charging and discharging impedance of the material; in short, under the joint action of specific long-range carbon nanotubes and their content and nano-silicon grains, the present invention effectively reduces the charging volume expansion, while improving the first reversible capacity and the first efficiency, so that the silicon-carbon negative electrode material has the characteristics of low expansion and long cycle.
[0027] In a preferred embodiment, the average particle size D50 of the silicon-carbon negative electrode material can be 0.5μm~15μm, and its typical but non-limiting average particle size D50 is, for example, 0.5μm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, and 15μm.
[0028] In a preferred embodiment, the pore volume of the silicon-carbon negative electrode material is less than 0.01 cm³ / g, the most probable pore diameter is less than 3 nm, and the specific surface area is ≤5 m² / g.
[0029] The specific parameters of the average particle size D50, pore volume, most probable pore size and specific surface area of the silicon-carbon negative electrode material in the present invention are more conducive to further reducing the charging volume expansion, further improving the first reversible capacity and first efficiency, and further improving the cycle life.
[0030] In a preferred embodiment, the resistivity of the silicon-carbon negative electrode material can be 10mΩ·cm~1000mΩ·cm, and its typical but non-limiting resistivity is, for example, 10mΩ·cm, 30mΩ·cm, 50mΩ·cm, 100mΩ·cm, 200mΩ·cm, 300mΩ·cm, 400mΩ·cm, 500mΩ·cm, 600mΩ·cm, 700mΩ·cm, 800mΩ·cm, 900mΩ·cm, and 1000mΩ·cm.
[0031] In a preferred embodiment, the grain size of nano silicon is less than 2 nm. A smaller silicon grain size is more conducive to reducing charging volume expansion and improving the first reversible capacity and first efficiency.
[0032] In the present invention, the proportion of nano-silicon in the silicon-carbon negative electrode material can be 10wt%~90wt%, and its typical but non-limiting proportion is, for example, 10wt%, 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, 80wt%, and 90wt%.
[0033] According to a second aspect of the present invention, there is provided a method for preparing the silicon-carbon negative electrode material as described in any one of the above, comprising the following steps: The hard carbon precursor containing long-range carbon nanotubes is pyrolyzed and carbonized and then activated to obtain porous carbon, and nano-silicon is deposited on the porous carbon to obtain a silicon-carbon negative electrode material.
[0034] The method for preparing the silicon-carbon negative electrode material provided by the present invention has simple process, high efficiency, high success rate and is suitable for industrial production.
[0035] In a preferred embodiment, after the nano-silicon deposition, the method further includes a step of coating the obtained silicon-carbon material.
[0036] In the present invention, the coating treatment method includes but is not limited to carbon coating by using a carbon source gas.
[0037] In a preferred embodiment, the method for preparing a hard carbon precursor containing long-range carbon nanotubes comprises the following steps: The carbon source, long-range carbon nanotubes and water are mixed and reacted to dehydrate and polymerize the carbon source to obtain a hard carbon precursor containing long-range carbon nanotubes; wherein the carbon source includes but is not limited to at least one of glucose, fructose, galactose, lactose, sucrose, maltose, rice starch, mung bean starch, wheat starch, cassava starch, corn starch, cellulose and phenolic resin.
[0038] In a preferred embodiment, the long-range carbon nanotubes include but are not limited to at least one of oligo-walled, single-walled and multi-walled carbon nanotubes after acid treatment.
[0039] In the present invention, the rich carboxyl and hydroxyl functional groups produced by acid treatment of long-range carbon nanotubes are hydrothermally combined with the hydroxyl-rich carbon source, so that the long-range carbon nanotubes can be evenly distributed inside the silicon-carbon negative electrode material to form a "reinforced concrete" structure; when the silicon-carbon material is embedded with lithium and expands, the long-range carbon nanotubes that are evenly distributed inside the material particles and have high strength can effectively restrain the expansion of the material.
[0040] In a preferred embodiment, the temperature of the mixed reaction of the carbon source, long-range carbon nanotubes and water can be 150°C~375°C, and typical but non-limiting temperatures are, for example, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 220°C, 240°C, 260°C, 280°C, 300°C, 325°C, 350°C, and 375°C; the pressure during the mixed reaction can be 2Mpa~8Mpa, and typical but non-limiting pressures are, for example, 2Mpa, 3Mpa, 4Mpa, 5Mpa, 6Mpa, 7Mpa, and 8Mpa.
[0041] The temperature and pressure of the mixed reaction of the carbon source, the long-range carbon nanotubes and water in the present invention are more conducive to further making the long-range carbon nanotubes evenly distributed in the hard carbon precursor.
[0042] In a preferred embodiment, the temperature for pyrolysis carbonization of the hard carbon precursor can be 800°C~1400°C, and typical but non-limiting temperatures are 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C, and 1400°C; the time for pyrolysis carbonization can be 1h~12h, and typical but non-limiting times are 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, and 12h.
[0043] The above-mentioned pyrolysis carbonization temperature and time are more conducive to further improving the formation effect of the porous carbon material.
[0044] In a preferred embodiment, the activation treatment may be at least one of a physical activation method and a chemical activation method.
[0045] In the present invention, the gas used in the physical activation method includes but is not limited to at least one of water vapor, air and carbon dioxide, which is more conducive to further improving the effect of the activation treatment.
[0046] In a preferred embodiment, the nano-silicon deposition method includes but is not limited to thermal decomposition deposition by silane compounds.
[0047] In the present invention, the temperature of pyrolysis deposition can be 300°C~800°C, and typical but non-limiting temperatures are, for example, 300°C, 400°C, 500°C, 600°C, 700°C, and 800°C; the time of pyrolysis deposition can be 1h~12h, and typical but non-limiting times are, for example, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, and 12h.
[0048] The temperature and time of the pyrolysis deposition are more conducive to further improving the deposition and dispersion effect of nano-silicon on the porous carbon.
[0049] A typical method for preparing a silicon-carbon negative electrode material comprises the following steps: (a) Long-range carbon nanotubes are uniformly distributed inside the hard carbon precursor during its generation process, thereby obtaining a hard carbon precursor containing long-range carbon nanotubes; (b) pyrolyzing and carbonizing the hard carbon precursor containing long-range carbon nanotubes in step (a) to obtain a porous carbon precursor containing long-range carbon nanotubes; (c) activating the porous carbon precursor containing long-range carbon nanotubes in step (b) to obtain a porous carbon material; (d) The porous carbon material of step (c) is subjected to pyrolysis treatment by respectively adsorbing silane compounds (nano-silicon deposition raw materials) and carbon source gas (carbon coating raw materials) to obtain a silicon-carbon negative electrode material.
[0050] According to a third aspect of the present invention, there is provided a use of the silicon-carbon negative electrode material described in any one of the above items in a lithium-ion secondary battery.
[0051] The application of the silicon-carbon negative electrode material provided by the present invention can effectively reduce the expansion of lithium-ion batteries, effectively increase the cycle life of lithium-ion batteries, and achieve outstanding application effects.
[0052] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.
[0053] Example 1 A method for preparing a low expansion and long cycle silicon-carbon negative electrode material comprises the following steps: S1: Add long-range carbon nanotube powder to a solution of concentrated sulfuric acid and concentrated nitric acid (ratio 3:1), ultrasonicate for 30 minutes, stir for 4 hours, dilute with water, filter, wash, and dry to obtain acid-treated single-walled long-range carbon nanotubes; mix 10kg of sucrose, 20g of acid-treated single-walled long-range carbon nanotubes (length 10μm, diameter 50nm) and 100kg of pure water in a high-pressure reactor, react at 200℃ for 5 hours to obtain a hard carbon precursor containing long-range carbon nanotubes; S2: The hard carbon precursor containing long-range carbon nanotubes is subjected to high-temperature carbonization at 800°C for 4 hours in a nitrogen atmosphere, and then subjected to air flow pulverization to obtain a porous carbon precursor containing long-range carbon nanotubes; S3: introducing carbon dioxide into the porous carbon precursor containing long-range carbon nanotubes in a rotary kiln for high-temperature activation at 900° C. for 12 h to obtain a porous carbon material; S4: Pyrolyzing the porous carbon material and monosilane in a CVD furnace at 500°C for 4h to deposit nano-silicon in the pore structure of the porous carbon to obtain a silicon-carbon precursor; Afterwards, acetylene was introduced at 550° C. for 2 h to coat the silicon-carbon precursor to obtain a silicon-carbon negative electrode material.
[0054] The physical and chemical parameters of the silicon-carbon negative electrode material of this embodiment are shown in Table 1, and its 2000 times scanning electron microscope image is shown in Figure 1 , its 30000 times scanning electron microscope image is shown in Figure 2 .
[0055] Example 2 The difference between this embodiment and embodiment 1 is that in step S1, sucrose is replaced with glucose; The remaining steps and their parameters are as in Example 1 to obtain a silicon-carbon negative electrode material. The physical and chemical index parameters are shown in Table 1.
[0056] Example 3 The difference between this embodiment and embodiment 1 is that in step S1, the single-walled long-range carbon nanotubes are replaced with multi-walled long-range carbon nanotubes; The remaining steps and their parameters are as in Example 1 to obtain a silicon-carbon negative electrode material. The physical and chemical index parameters are shown in Table 1.
[0057] Example 4 The difference between this embodiment and embodiment 1 is that in step S1, sucrose is replaced with corn starch; The remaining steps and their parameters are as in Example 1 to obtain a silicon-carbon negative electrode material. The physical and chemical index parameters are shown in Table 1.
[0058] Example 5 The difference between this embodiment and embodiment 1 is that in step S4, the temperature of pyrolysis of monosilane is 600°C; The remaining steps and their parameters are as in Example 1 to obtain a silicon-carbon negative electrode material. The physical and chemical index parameters are shown in Table 1.
[0059] Example 6 The difference between this embodiment and embodiment 1 is that in step S3, carbon dioxide is replaced with water vapor; The remaining steps and their parameters are as in Example 1 to obtain a silicon-carbon negative electrode material. The physical and chemical index parameters are shown in Table 1.
[0060] Example 7 The difference between this embodiment and embodiment 1 is that in step S1, the amount of long-range carbon nanotubes added is changed to 100 g; The remaining steps and their parameters are as in Example 1 to obtain a silicon-carbon negative electrode material. The physical and chemical index parameters are shown in Table 1.
[0061] Example 8 The difference between this embodiment and embodiment 1 is that in step S1, the amount of long-range carbon nanotubes added is changed to 2 g; The remaining steps and their parameters are as in Example 1 to obtain a silicon-carbon negative electrode material. The physical and chemical index parameters are shown in Table 1.
[0062] Comparative Example 1 The difference between this comparative example and Example 1 is that in step S1, no long-range carbon nanotubes are added; The remaining steps and their parameters are as in Example 1 to obtain a silicon-carbon negative electrode material. The physical and chemical index parameters are shown in Table 1.
[0063] Comparative Example 2 The difference between this comparative example and Example 1 is that in step S1, the long-range carbon nanotubes are replaced with conductive carbon black; The remaining steps and their parameters are as in Example 1 to obtain a silicon-carbon negative electrode material. The physical and chemical index parameters are shown in Table 1.
[0064] Comparative Example 3 The difference between this comparative example and Example 1 is that in step S1, the long-range carbon nanotubes are replaced with short-range carbon nanotubes; The remaining steps and their parameters are as in Example 1 to obtain a silicon-carbon negative electrode material. The physical and chemical index parameters are shown in Table 1.
[0065] Test Example 1 The physical and chemical index parameters of the silicon-carbon negative electrode materials obtained in Examples 1-8 and Comparative Examples 1-3 are shown in Table 1.
[0066] The particle size (μm) range of the material was tested using Dandong Better Laser Particle Sizer BT-9300ST; The specific surface area (m² / g) of the material was tested using JW-DX dynamic adsorption specific surface area meter. The resistance of the powder is accurately measured using GEST-126. The material was analyzed by XRD diffractometer (Panalytical X'PERT PRO MPD, Netherlands) to determine the grain size of the material; The pore size distribution of the material was tested using the American Quantachrome Autosorb IQ3.
[0067] Table 1
[0068] It can be seen from Table 1 that in Examples 1-8 and Comparative Examples 1-2, the content and type of long-range carbon nanotubes have a great influence on the resistivity of the material; it can be seen from the data of Example 8, Example 1 and Example 7 that with the increase of the long-range carbon nanotube content, the resistivity of the silicon-carbon negative electrode material is significantly reduced; it can be seen from the data of Example 1 and Example 3 that, at the same addition ratio, the resistivity of the material after the addition of multi-walled long-range carbon nanotubes is higher; no conductive agent was added in Comparative Example 1, resulting in the highest resistivity of the silicon-carbon negative electrode material; conductive carbon black was added in Comparative Example 2, and although the resistivity of the silicon-carbon negative electrode material was reduced, it was still relatively high; short-range carbon nanotubes were added in Comparative Example 3, and the resistivity of the silicon-carbon negative electrode material was still relatively high; in Example 5, due to the high temperature of silane thermal decomposition, the size of the silicon grains was also larger.
[0069] Test Example 2 The first reversible capacity and first efficiency of the obtained silicon-carbon negative electrode material were tested as follows: Silicon-carbon negative electrode material, conductive carbon black and binder are mixed in pure water at a mass ratio of 94.5:1.5:4, homogenized, and the solid content is controlled to be 48wt%, coated on a copper foil current collector, vacuum-baked at 100°C for 8h, pressed and formed, and then punched to prepare a negative electrode sheet; The button half-cell was assembled in a glove box filled with argon. The counter electrode was a metal lithium sheet, the separator used was PE, and the electrolyte was 1 mol / L LiPF6 EC / DMC (Vol 1:1). Carry out charge and discharge test on button batteries, the test process is 0.1C DC to 0.005V, 0.05C DC to0.005V, 0.02C DC to 0.005V, Rest 10min, 0.1C CC to 1.5V; The first reversible capacity and efficiency of silicon-carbon anode materials were measured; Among them, the button battery testing equipment is the LAND battery testing system of Wuhan Landian Electronics Co., Ltd.
[0070] The expansion rate test of silicon-carbon negative electrode material S600 is as follows: The silicon-carbon negative electrode material is measured for the first reversible capacity by the above-mentioned charge-withdrawal test method, and then a certain amount of the same graphite negative electrode is mixed according to the calculation to mix the silicon-carbon negative electrode material to 600±5mA·h / g, abbreviated as S600; The S600 mixed material, conductive carbon black and binder (mass ratio 92:2:6) were homogenized in pure water, the solid content was controlled to 48wt%, and the mixture was coated on a current collector with a copper foil as the substrate, and then vacuum-baked at 90°C for 8h, pressed by a roller press, and then sliced by a slicing device to prepare a negative electrode sheet; the thickness of the negative electrode sheet was measured by a micrometer and recorded as T1, and the thickness of the substrate was measured as T2, and the data were recorded; Assemble button half-cells in an argon-filled glove box, with the counter electrode being a metal lithium sheet, the separator being a PE material, and the electrolyte being 1 mol / L LiPF6 EC / DMC (Vol 1:1); perform charge and discharge tests on the button cell, with the test process being 0.1CDC to 0.005V, 0.05C DC to 0.005V, 0.02C DC to 0.005V, Rest 10min, 0.1C CC to1.5V, 0.1C DC to 0.005V, 0.05C DC to 0.005V, 0.02C DC to 0.005V; measure the first reversible capacity and efficiency of the negative electrode material; The battery is disassembled, and the thickness of the negative electrode material obtained by the disassembly is detected and recorded as T3; the first full-charge expansion data of the negative electrode material is calculated according to the formula F=(T3-T1) / (T1-T2), and F is the first full-charge expansion rate; The button cell testing equipment is the LAND battery testing system of Wuhan Landian Electronics Co., Ltd.; the slicing equipment is the MSK-T10 button half-cell slicing equipment of Kejing; the micrometer detection equipment is the Japanese Mitutoyo 293-100-10; and the rolling equipment is the MSK-HRP-05 button half-cell slicing equipment of Kejing.
[0071] The capacity retention rate test of silicon-carbon negative electrode material is as follows: The silicon-carbon negative electrode material powder is mixed with the graphite negative electrode (mass ratio is 10~80:20~90) to obtain a mixed negative electrode powder, and then the negative electrode powder, Super p and BP-7 are mixed in pure water at a mass ratio of 92:4:4, and the solid content is controlled at 48wt%. After slurrying, it is coated on a current collector with a copper foil as the substrate, placed in a vacuum baking oven at 80℃-100℃ for vacuum baking for 4h-8h, and the pole piece is cold pressed with a commercial roller pressing equipment of Kejing, and the pole piece is sliced into small discs with a diameter of 15mm-22mm using a commercial slicing equipment of Kejing to prepare a silicon composite negative electrode pole piece; commercial 523 positive electrode material, SP and PVDF (polyvinylidene fluoride) are mixed with an appropriate amount of NMP (N-methyl pyrrolidone) solvent, control the solid content to 55wt%, apply the mixed slurry on the current collector with aluminum foil as the substrate, place it in a vacuum oven at 90℃-120℃ for vacuum baking for 4h-8h, use Kejing commercial roller pressing equipment to cold press the pole piece, use Kejing commercial slicing equipment to slice the pole piece into small discs with a diameter of 15mm-22mm to prepare the positive pole piece; dry it at 85℃ vacuum (-0.1MPa) for 8h, weigh and calculate the weight of the active material; the separator used is PE, and the electrolyte is 1mol / L LiPF6 EC / DMC (Vol 1:1); assemble it into a CR2430 button-type full battery in a glove box; The button-type full battery was left at room temperature for 2h-6h, activated by charge and discharge at 0.1C on the Blue Electric test system, and then cycled at 1C (voltage range 3.0V-4.2V) for 20-300 cycles; the capacity retention rate of the material = discharge capacity of the last cycle / discharge capacity of the first cycle × 100%.
[0072] The above test results are shown in Table 2, and the first charge and discharge curve of the lithium button battery of the silicon-carbon negative electrode material of Example 1 is shown in Figure 3 The first charge and discharge dQ / dV curve of the lithium button cell of the silicon-carbon negative electrode material of Example 1 is shown in Figure 4 .
[0073] Table 2
[0074] It can be seen from Table 2 that the silicon-carbon negative electrode materials prepared in Examples 1-8 have higher first reversible capacity and rate retention rate. In the lithium-ion battery test system, the first reversible capacity can reach above 1850 mA·h / g; the first reversible capacity of the silicon-carbon negative electrode materials prepared in Comparative Examples 1-2 is relatively low, mainly due to the large specific surface area and pore volume. It can be seen from the data of Examples 1-8 and Comparative Examples 1-2 that the content and type of long-range carbon nanotubes have a great influence on the expansion and cycle of the material; it can be seen from the data of Example 8, Example 1 and Example 7 that with the increase of the content of long-range carbon nanotubes, the first expansion rate of S600 is significantly reduced, and the 1000-week cycle retention rate is significantly improved; it can be seen from Example 1 and Example 3 that, at the same addition ratio, the expansion and cycle performance of the material are better after the addition of single-walled carbon nanotubes; no conductive agent was added in Comparative Example 1, resulting in the worst expansion and cycle performance of the silicon-carbon negative electrode material; conductive carbon black was added in Comparative Example 2, and although the resistivity of the silicon-carbon negative electrode material was reduced, the expansion and cycle performance were still poor; short-range carbon nanotubes were added in Comparative Example 3, and the expansion and cycle performance of the silicon-carbon negative electrode material were still poor; although the grain size of the silicon-carbon negative electrode material prepared in Example 5 is larger, due to the presence of long-range carbon nanotubes, the expansion and cycle performance are still good.
[0075] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A silicon-carbon negative electrode material, characterized in that: It comprises porous carbon and nano-silicon dispersed on the porous carbon; The porous carbon includes pyrolytic carbon and long-range carbon nanotubes dispersed in the pyrolytic carbon; The long-range carbon nanotubes account for 0.1wt% to 5wt% of the silicon-carbon negative electrode material; The long-range carbon nanotubes have a length of 2 μm to 20 μm and a diameter of 1 nm to 100 nm.
2. The silicon-carbon negative electrode material according to claim 1, characterized in that: The average particle size D50 of the silicon-carbon negative electrode material is 0.5 μm to 15 μm; The pore volume of the silicon-carbon negative electrode material is less than 0.01 cm³ / g, the most probable pore diameter is less than 3 nm, and the specific surface area is ≤5 m² / g.
3. The silicon-carbon negative electrode material according to claim 1 or 2, characterized in that: The resistivity of the silicon-carbon negative electrode material is 10 mΩ·cm to 1000 mΩ·cm.
4. The silicon-carbon negative electrode material according to claim 1 or 2, characterized in that: The grain size of the nano-silicon is less than 2nm; The nano-silicon accounts for 10wt% to 90wt% of the silicon-carbon negative electrode material.
5. A method for preparing the silicon-carbon negative electrode material according to any one of claims 1 to 4, characterized in that: The following steps are involved: The hard carbon precursor containing long-range carbon nanotubes is pyrolyzed and carbonized and then activated to obtain porous carbon, and nano-silicon is deposited on the porous carbon to obtain the silicon-carbon negative electrode material.
6. The preparation method according to claim 5, characterized in that: After the nano-silicon deposition, the step of coating the obtained silicon-carbon material is also included; The coating treatment method includes carbon coating through a carbon source gas.
7. The preparation method according to claim 5, characterized in that: The method for preparing the hard carbon precursor containing long-range carbon nanotubes comprises the following steps: Mixing a carbon source, long-range carbon nanotubes and water to react, dehydrating and polymerizing the carbon source to obtain the hard carbon precursor containing the long-range carbon nanotubes; The carbon source comprises at least one of glucose, fructose, galactose, lactose, sucrose, maltose, rice starch, mung bean starch, wheat starch, cassava starch, corn starch, cellulose and phenolic resin; The long-range carbon nanotubes include at least one of oligo-walled, single-walled and multi-walled carbon nanotubes after acid treatment; The temperature of the mixed reaction is 150°C to 375°C; The pressure of the mixed reaction is 2Mpa~8Mpa.
8. The preparation method according to claim 5, characterized in that: The temperature of the pyrolysis carbonization is 800°C to 1400°C; The pyrolysis carbonization time is 1h~12h.
9. The preparation method according to claim 5, characterized in that: The activation treatment includes at least one of a physical activation method and a chemical activation method; The gas used in the physical activation method includes at least one of water vapor, air and carbon dioxide; The nano-silicon deposition method includes thermal decomposition deposition through silane compounds; The temperature of the pyrolysis deposition is 300°C to 800°C; The pyrolysis deposition time is 1 h to 12 h.
10. Use of the silicon-carbon negative electrode material according to any one of claims 1 to 4 in a lithium-ion secondary battery.
Citation Information
Patent Citations
Composite conductive agent, lithium ion battery pole pieces and lithium ion battery
CN107482222A
Negative electrode material, negative electrode sheet, electrochemical device, and electronic device
CN113728471A
Silicon-carbon negative electrode material and preparation method and application thereof
CN116799194A
Silicon-carbon composite material and preparation method therefor, secondary battery and electric device
WO2024040605A1
